Estudio de prefactibilidad para la instalación de una planta productora de parches reforzados con colágeno tipo I a base de piel de tilapia de Nilo (Oreochromis niloticus) - Montero Sandoval, Francis Carlos (2021)
Today there are many possible ways of treatment for skin burns, differing in complexity, costs, difficulty in treatment and other factors. In Brazil in 2017, the university of Ceará showed favorable results in the application of a new method for the treatment of second-degree and third-degree burns, applying tilapia skin and ointment to clean and calm the pain. The patient benefited with a reduced healing time, less expensive treatment and it was not necessary to change the band covering the wound as it normally would. This success drove many researchers to concentrate on the properties from the tilapia skin, relating its efficiency due to the amount of type I collagen concentrated found on this animal skin. This research evaluates the technological and economic prefeasibility on installing a plant of gauzes made of tilapia skin for treatment of first-degree and second-degree burns. Since this health technology is new, it represents a challenge to schematize the actual handmade sterilization process of the tilapia skin and industrialize it, looking for profitability in the mass production of this new product. To achieve that, we applied the scientific method, engineer tools for the localization, cost, and plant layout. Also, a market research to evaluate and project de current demand in the Peruvian market.